Assessment of physical and mental health of an elderly woman with depression symptoms: An experience report (Research, Society and Development, 2024)
The objective of this study was to develop and implement an interdisciplinary care plan for an 80-year-old woman with signs of depression, aiming to improve her quality of life. The care plan sought to strengthen her autonomy, physical and emotional well-being, and social reintegration, considering her needs. The study was conducted as part of the IESC course at the AFYA Faculdade de Ciências Médicas de Bragança, through home visits with Community Health Agents (ACS), between August and October of 2024. Data collection involved medical history, physical exams, and the application of scales such as the Beck Depression Inventory, the Clinical Functional Vulnerability Index-20, and the Timed Up and Go Test. Additionally, a genogram, ecomap, and the APGAR-family questionnaire were used to analyze the patient's social context. The results indicated that the elderly patient exhibited symptoms of moderate depression and frailty but with no elevated fall risk. The care plan included short-, medium--, and long-term goals, such as encouraging social activity, providing psychological support, and ensuring adherence to medical treatments. The Singular Therapeutic Project succeeded in identifying mental health issues and coordinating the care network, promoting a comprehensive and humanized approach.